Microsatellite abnormalities in plasma of patients with breast carcinoma: concordance with the primary tumour. Issue 5 (1st May 1999) - Mayall, F; Fairweather, S; Wilkins, R; Chang, B; Nicholls, R
Abstract : AIMS: To detect microsatellite abnormalities in the primary tumours and plasma of patients with breast carcinoma. METHODS: Plasma was obtained from 17 breast carcinoma patients before surgery. Corresponding tumour and benign lymph node (control) samples for each of the carcinoma patients were obtained from paraffin blocks. DNA was extracted from the plasma samples and the paraffin embedded tissue using previously described methods. RESULTS: The 17 primary tumours showed two examples of loss of heterozygosity and three examples of microsatellite instability; the 17 plasma samples showed three and one, respectively. Many of the longer microsatellites (over 200 base pairs) were difficult to amplify from plasma. The investigations suggested that this was because of the highly fragmented nature of plasma DNA. Only one example of loss of heterozygosity and one example of microsatellite instability showed a concordant pattern in both primary tumour and plasma. These were both in the same patient. CONCLUSIONS: DNA mutations concordant with those in the primary carcinomas can occasionally be detected in the plasma of patients with breast carcinoma. However, the frequency would have to be markedly improved before this could be of any diagnostic value.